2013 IEEE International Reliability Physics Symposium (IRPS) 2013
DOI: 10.1109/irps.2013.6531956
|View full text |Cite
|
Sign up to set email alerts
|

Technology scaling on High-K & Metal-Gate FinFET BTI reliability

Abstract: High-K (HK) & Metal-Gate (MG) transistor technology have become a mainstream for the logic & SOC processes. On HK/MG process, bias-temp instability (BTI) poses continuous challenges on the technology scaling despite the reduced Vcc. In recent technologies, PMOS NBTI degradation is increased while NMOS PBTI was reduced with HK scaling.Interfacial Layer (IL) scaling underneath the HK that affects PMOS NBTI and device performance is very challenging. Impact of technology scaling on BTI and BTI on FinFET technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…We modelled degradations and improvements in routing resources with the model (10). We note in Table 4 the parameters γ, Ea and b, which are similar for all RO architectures.…”
Section: Modelling Routing Resources Degradations Under Static Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…We modelled degradations and improvements in routing resources with the model (10). We note in Table 4 the parameters γ, Ea and b, which are similar for all RO architectures.…”
Section: Modelling Routing Resources Degradations Under Static Stressmentioning
confidence: 99%
“…Intel also shows in [ 9 ] that PBTI decreases in the 22 nm FinFET compared with the 32 nm HKMG MOSFET; however, a slight increase in NBTI is observed in the FinFET. In [ 10 ], the author reveals that the NBTI recovery mechanism is more important in a 20 nm MOSFET than in a 14 nm FinFET, which may explain why the overall degradation due to NBTI is greater in the FinFET [ 9 ]. A simulation based on the diffusion–reaction model of a 16 nm MOSFET and FinFET is performed in [ 11 ] and indicates that the propagation delay degradation is higher in MOSFET.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging related degradation mechanisms like NBTI are strongly a function of workload/activity pattern at the gate input of the transistor due to the observed recovery effects [4], [13]. In [10], an Adaptive Workload Splitting (AWS) algorithm and a long-term extrapolation methodology were proposed for fast calculation of NBTI degradation due to an arbitrary nonuniform activity pattern with excellent accuracy.…”
Section: A the Proposed Workload Dependent Aging Aware Design Flowmentioning
confidence: 99%
“…Figure 3.12 shows the absolute shift of the V T for a 14nm pFinFET at 125 • C under the time and voltage acceleration. Figure 3.12: V T shift due to BTI under time and voltage acceleration in 14nm pFinFET [84] It has been shown that BTI recovery in tri-gate devices matches data and model predictions from planar devices [85], also just as in planar devices increasing temperature can enhance the recovery in tri-gate devices [86]. Regarding these, Figure 3.13 shows the recovery characteristics between planer (20nm) and FinFET devices (14nm).…”
Section: Reliability-aware Memory Design Using Advanced Reconfigurati...mentioning
confidence: 61%